Literatura in mediji v Jurčičevem času - Dović, Marijan (Slavistična revija, 2006)
The study ties the rapid development of literary prose in the second half of the 19th century with the contemporary naissance of the media metwork, i.e., publishing houses, newspapers, and literary journals. The media provided the sufficient structural oppurtunities for publishing and activities in various roles of the literary system. The development is presented on the example of one of the leading narrative prose writer of this area, Josip Jurčič.
Keywords: časopisi; Jurčič, Josip; literarna sociologija; literarni sistem; literarno posredovanje; literary mediation; literary sociology; literary system; media system; medijski sistem; newspapers; publishing; Slovene literature; slovenska književnost; založništvo